Hubungan Kadar Kolesterol Total dengan Tekanan Darah pada Penderita Diabetes Mellitus Tipe 2 Layanan Kesehatan Primer - Putri Amellia Sari; Chairil Anwar; Arifiani Agustin Amalia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Type 2 Diabetes Mellitus (T2DM) was a chronic metabolic disease characterized by hyperglycemia caused by insulin resistance and impaired insulin secretion. This condition is often accompanied by dyslipidemia, which may increase the risk of atherosclerosis and changes in blood pressure. This reseach was purposelly to established the relation among total cholesterol grades also blood pressure in patients with T2DM at Mantrijeron Community Health Center. This reseach was analyzing observational design with a cross-sectional approach use secondary data included from the medical records of T2DM patients from June to December 2025. The reseach population total of 105 patients, also amount 67 patients who met the inclusion and exclusion criteria were selecting using purposive sampling. The respondents were predominantly aged 45–54 years (53.73%) and female (82.09%). Data were analyzing use the Kolmogorov–Smirnov normality test and Spearman correlation test. The yields shown that most respondents has normal total cholesterol grades (<200 mg/dL), accounting for 45 patients (67.16%), systolic blood pressure in the prehypertension category, accounting for 45 patients (67.16%), and normal diastolic blood pressure (≤80 mmHg), accounting for 29 patients (43.38%). The correlation analysis shown that dont has significant relation among total cholesterol grades also systolic blood pressure (p = 0.645) or diastolic blood pressure (p = 0.658). the yields was including total cholesterol grades dont has significantly associated with either systolic or diastolic blood pressure in patients with T2DM at Mantrijeron Community Health Center.